PEMANFAATAN BUAH PEPAYA (Carica Papaya L.,) DAN TOMAT (Lycopersicum Esculentum MILL.,) DALAM PEMBUATAN FRUIT LEATHER - Redi Ramli; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed was to got exact formulation of combination of papaya fruit puree and tomato puree in the manufacture of fruit leather. This study used a completely randomized design (CRD) with 5 treatments and 3 replications. The treatments used against fruit leather were PT1 (papaya fruit puree 65%, tomato puree 35%), PT2 (papaya fruit puree 55%, tomato puree 45%), PT3 (papaya fruit puree 50%, tomato puree 50%), PT4 (45% papaya fruit puree, tomato puree 55%) and PT5 (35% papaya fruit puree, tomato puree 65%). Data were analyzed statistically using ANOVA and DNMRT at 5% level. The results showed that the use of papaya fruit puree and tomato puree significantly effect on water content, ash content, acidity (pH), fiber content, total sugar content and sensory analysis. Fruit leather chosen from the results of this study was fruit leather treatment PT2 which has moisture content 11,86%, ash content 1,03%, degree of acidity 4,39, fiber content 3,12%, levels total sugar 36,45%, reddish orange color, flavor slightly fruity papaya and tomatoes, slightly sour taste, chewy texture and overall assessment fruit leather preferred by the panelists. Keywords : Fruitleather, papaya fruit puree and tomato puree.